(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Excess iodine is known to affect thyroid function, and in predisposed individuals even a moderately increased iodine intake may cause hypothyreosis or hyperthyreosis. In our material, one patient developed hypothyreosis and five patients hyperthyreosis after using commercial health products containing iodine.